Modelling photovoltaic systems using PSpice - Castaner, Luis, ....-; Silvestre, Santiago, ....- (Chichester : Wiley, 2002)
Introduction to Photovoltaic Systems and Pspice.Spectral Response and Short Circuit Current.Electrical Characteristics of the Solar Cell.Solar Cell Arrays PV Modules and PV Generators.Interfacing PV Modules to Loads and Battery Modelling.Power Conditioning and Inverter Modelling.Stand - Alone PV Systems.Grid Connected PV Systems.Small Photovoltaics.
Keywords: Elektrische voeding; Zonne-energie elektriciteitsvoorzieningen